Unraveling the synergy of radiotherapy and immune checkpoint inhibitors in NSCLC: emerging clinical evidence and novel therapeutic strategies - Ismaili, Khalil-elmehdi; Fenneteau, Frédérique; Bruneau, Jérémy; Schirru, Miriam; Charef, Hamza; Zugaj, Didier; Tremblay, Pierre-Olivier; Nekka, Fahima (Frontiers in Oncology, 2025)
Non-small cell lung cancer (NSCLC) remains the leading cause of cancer-related mortality worldwide. While immune checkpoint inhibitors (ICIs) continue to redefine the therapeutic paradigm, their efficacy is limited to a specific proportion of patients. Radiotherapy (RT) is proposed as a strategy to enhance their efficacy, yet its clinical impact remains unclear, hindered by its double-edged sword effect on the immune system across variable settings. This review explores the landscape of RT-ICI combinations in NSCLC, analyzing available evidence in the light of current treatment guidelines. The presented data provide a foundation to validate computational models to predict clinical outcomes and inform tumor-immune dynamics. ClinicalTrials.gov was queried for trials involving both modalities, excluding studies incorporating other therapies except chemotherapy and surgery, other cancer types, or brain metastases. Of the 309 trials identified, 23 met the inclusion criteria, encompassing resectable (n=3), early-stage (n=3), locally advanced (n=10), and advanced NSCLC (n=7). In the neoadjuvant setting, the combination achieves a remarkable pathological response without significantly affecting surgical outcomes. Long-term survival benefit remains elusive. In early-stage unresectable tumors, ICIs are poised to replace chemotherapy as the preferred peri-radiation systemic treatment to prevent recurrences. Current data on locally advanced NSCLC confirm the feasibility of early ICI introduction, chemotherapy-free regimens, and individualized RT approaches. A definitive risk-benefit balance has yet to be established. In advanced stages, while the abscopal effect is well documented, statistical significance remains a concern, necessitating adequately designed studies powered to identify subpopulations most likely to benefit from the combination. Innovative, feasible approaches include RT and dual ICI, re-irradiation beyond progression, multisite micro-radiation, or partial irradiation of large tumors to activate a “hot” tumor microenvironment. In conclusion, while the combination of RT and ICI holds promise, significant challenges remain. A deeper understanding of immune dynamics is crucial. Additionally, the complexity of trial design, coupled with a lack of statistical significance in most available data, underscores the need for more phase 3 trials, the development of powerful biomarkers, and complementary approaches, such as virtual clinical trials, to accelerate progress and refine treatment strategies.